The research of individual macroeconomic effects of the impact of innovative entrepreneurship on economic growth in BRICS countries - B. D. Matrizaev (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. This article is devoted to the study of individual macroeconomic effects of the impact of innovative entrepreneurship on economic growth in the fast-growing BRICS member countries. Despite the fact that innovative entrepreneurship has recently attracted a lot of attention in theoretical and methodological aspects due to its enormous impact on economic growth in technologically leading countries, there are few in-depth empirical studies that pay sufficient attention to the explicit relationship between innovative entrepreneurship and economic growth in new countries, forming a system of neo-global equilibrium and economic growth in the global economy.Goal. The purpose of this article is to explore the potential relationship between innovative entrepreneurship and economic growth, focusing on the fast-growing economies of BRICS countries (Brazil, Russia, India, China and South Africa).Materials and methods. The study uses analytical data for the period from 2002 to 2022 and a number of econometric tools for macroeconomic assessment, including the combined least squares model, fixed effects, generalized least squares and two-stage least squares methods.Results and discussion. The results of the empirical analysis show that innovative entrepreneurship has a positive and signifycant impact on economic growth in the BRICS countries. Similarly, the openness of trade and the growth of physical capital stocks also contributed to overall economic growth.Conclusion. A positive relationship between human capital and economic growth has been revealed, which is statistically significant for the economies of the BRICS countries. Finally, the verification of the causal relationship revealed a one-sided relationship directed from innovative entrepreneurship to economic growth.